2016
DOI: 10.5664/jcsm.6182
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea Increases the Perioperative Risk of Cardiac Valve Replacement Surgery: A Prospective Single-Center Study

Abstract: RVHD patients with OSA have an increased incidence of perioperative adverse events. OSA was independently associated with overall postoperative recovery, respiratory insufficiency, and higher rate of postoperative pacemaker use, while CSA was not associated with postoperative events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…Undiagnosed OSA is an incognitive risk factor for prolonged ICU stay after TAAD repair. Although the mechanism has not been elucidated thoroughly, results from previous studies have indicated that OSA is associated with postoperative complications after cardiac and non-cardiac surgeries [10][11][12], and this might prolong ICU stay and worsen surgical outcomes. The current study shows that severe OSA predicts postoperative hypoxemia, which in turn is a strong predictor of prolonged ICU stay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Undiagnosed OSA is an incognitive risk factor for prolonged ICU stay after TAAD repair. Although the mechanism has not been elucidated thoroughly, results from previous studies have indicated that OSA is associated with postoperative complications after cardiac and non-cardiac surgeries [10][11][12], and this might prolong ICU stay and worsen surgical outcomes. The current study shows that severe OSA predicts postoperative hypoxemia, which in turn is a strong predictor of prolonged ICU stay.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that obstructive sleep apnoea (OSA) is associated with the onset of aortic dissection through arterial dysfunction, hypertension, and augmented negative thoracic pressure [7][8][9]. Patients with OSA can have poor short-term prognosis as they are at risks of developing hypoxemia after cardiac and non-cardiac surgeries [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…However, we fully agree that the associated morbidity was not negligible, with significant postoperative complications and increased length of stay. Sleep-disordered breathing is highly prevalent in obese patients [ 8 ] with associated upper airway muscle weakness, vascular endothelial dysfunction, cardiac arrhythmia, alveolar hypoventilation and sensitivity to anaesthetic medications leading to sudden cardiovascular death, myocardial infarction, stroke, worsening overall postoperative recovery and higher pacemaker use [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated that OSA is associated with postoperative complications including respiratory events, cardiac complications, intensive care unit admissions, and increased length of hospital stay. [2][3][4][5][6][7][8][9] Within the elective surgical population, it is estimated that 20% to 70% have OSA, and approximately 80% are undiagnosed at the time of surgery. 10,11 Patients with undiagnosed OSA may unknowingly be at increased risk for perioperative complications.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, patients presenting for surgery and undergoing general anesthesia may be at risk for significant postoperative events. Multiple studies have demonstrated that OSA is associated with postoperative complications including respiratory events, cardiac complications, intensive care unit admissions, and increased length of hospital stay . Within the elective surgical population, it is estimated that 20% to 70% have OSA, and approximately 80% are undiagnosed at the time of surgery .…”
Section: Introductionmentioning
confidence: 99%